A Guide to Industry Payments and an Algorithm for Their Management. Issue 1 (January 2022) - Isbester, Kelsey A.; Boas, Samuel R.; Wee, Corinne; Summerville, Lesley; Kumar, Anand R.
Abstract : Background: The Open Payments database was created to increase transparency of industry payment relationships within medicine. The current literature often examines only 1 year of the database. In this study, the authors use 5 years of data to show trends among industry payments to plastic surgeons from 2014 to 2018. In addition, the authors lay out the basics of conflict-of-interest reporting for the new plastic surgeon. Finally, the authors suggest an algorithm for the responsible management of industry relationships. Methods: This study analyzed nonresearch payments made to plastic surgeons from January 1, 2014, to December 31, 2018. Descriptive statistics were calculated using R Statistical Software and visualized using Tableau. Results: A total of 304, 663 payments totaling $140, 889, 747 were made to 8148 plastic surgeons; 41 percent ($58.28 million) was paid to 50 plastic surgeons in the form of royalty or license payments. With royalties excluded, average and median payments were $276 and $25. The average yearly total per physician was $2028. Of the 14 payment categories, 95 percent of the total amount paid was attributable payments in one of six categories. Seven hundred thirty companies reported payments to plastic surgeons from 2014 to 2018; 15 companies (2 percent) were responsible for 80 percent ($66.34 million) of the total sum paid. Allergan was responsible for $24.45 million (29.6 percent) of this amount. Conclusions: Although discussions on the proper management of industry relationships continue to evolve, the data in this study illustrate the importance of managing industry relationships. The simple guidelines suggested create a basis for managing industry relationships in the career of the everyday plastic surgeon.